LENGTH-WEIGHT RELATIONSHIP OF TWO GOBIDS BOLEOPHTHALMUS BODDARTI (PALLAS, 1770) AND BOLEOPHTHALMUS DUSSUMIERI (VALENCIENNES, 1837) OF MUMBAI COAST, INDIA - Ruhi Jaiswar; Bhavita Chavan; P.P. Srivastava (Journal of Indian Fisheries Association, 2018)
The present study deals with LWR and condition factor of two gobid species, Boleoplathalmus boddarti and B. dussumieri (Oxudercine gobies). distributed along the mudflats of Elephanta Islands, and Bhayander creek Mumbat, India. The length weight relationship has an extensive importance in fishery research. especially in fish population dynamics and growth. The measured length and weight of both the gobids varied between 70 and 180mm. and 5 to 35 gms, respectively. The L-W relationships are established as Log W= -4.409+2.799 log L for B. boddarti and Log W=5.417+3.101 Log L for B. dussumieri with r2 = 0.924 and r = 0.809, respectively. Growth in B. boddarti was found to be negative while in B dussumieri a positive allometric (p> 3). Fultons condition factor K ranged from 0.38 to 0.74 in both the species which indicates that the habitat is not ideal for the gobies to thrive on, at this point of time, on account of pollution. The study provides first biological reference on less studied species and can serve as a basis for management and conservation of these species